Condições do humor aquoso, quanto à contaminação, na facoemulsificação com implante de lente intraocular em cães - Lacerda, Luciana de Cenço Corrêa de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Phacoemulsification is the surgical treatment most commonly performed and accepted for cataracts. The use of artificial intraocular lens (IOL), indicated to achieve emetropy and as an aid on the prophylaxis of posterior capsule opacification, may, however, give rise to contamination arising from the nasal cavity and palpebral conjunctiva, in addition to the environment, the surgical staff, materials and instrumental. The goal of this research was to identify strains of bacteria present in the nasal and conjunctival secretions and aqueous humor of dogs undergoing phacoemulsification with implantation of intraocular lenses, as well as the characterization of genetic diversity among populations found using it sequencing of 16S rDNA of microorganisms, after selection of different groups by Rep-PCR with the primer BoxA1 associated BoxC1R. This study founded genders of bacteria like Enterobacter, Staphylococcus, Streptococcus and Pantoea and Staphylococcus aureus species. PCR-RFLP, using the enzyme MboI, identified Staphylococcus species such as S. pseudointermedius. Two copies of coagulase positive Staphylococcus aureus, founded by PCR, were confirmed by biochemical coagulase test. All of isolates was submitted by Rep-PCR with molecular markers Rep1R-I associated with Rep2, Eric2 and BoxC1R. It was found high genetic variability among them, especially regarding the gender Staphylococcus. Sequencing of 16S rDNA and Rep-PCR were effective in detecting genetic diversity. Eight isolates of gender Enterobacter in the conjunctival secretion and, at the same time, in aqueous humor, showed genetic distance of 0.000. Five percent of patients submitted to phacoemulsification with IOL implantation showed contamination in aqueous humor, by Enterobacter spp

O tratamento cirúrgico para a catarata, pela facoemulsificação, é atualmente o mais aceito e praticado. A utilização de lentes intraoculares (LIO), indicadas para a correção da emetropia e para a profilaxia da opacificação da cápsula posterior, pode, todavia, ensejar contaminação advinda da cavidade nasal e da conjuntiva palpebral, além do ambiente, da equipe cirúrgica, de materiais e de instrumentais. Com o trabalho, objetivou-se a identificação de linhagens de bactérias presentes nas secreções nasal e conjuntival e no humor aquoso de cães submetidos à facoemulsificação com implante de lentes intraoculares, bem como a caracterização da diversidade genética entre as populações encontradas, empregando-se o sequenciamento da região 16S rDNA de microrganismos, após seleção de diferentes grupos pela Rep-PCR, com o primer BoxA1 associado ao BoxC1R. Encontraram-se bactérias dos gêneros Enterobacter, Staphylococcus, Streptococcus e Pantoea e a espécie Staphylococcus aureus. Pela PCR-RFLP, utilizando-se a enzima MboI, identificaram-se espécies de Staphylococcus, como o S. pseudointermedius. Foram encontrados dois exemplares de Staphylococcus aureus coagulase positivo, pela PCR, confirmados pelo teste bioquímico da coagulase. Os isolados foram submetidos à Rep-PCR com marcadores moleculares Rep1R-I associado ao Rep2, Eric2 e BoxC1R. Encontrou-se alta variabilidade genética entre eles, notadamente quanto ao gênero Staphylococcus. O sequenciamento da região 16S rDNA e a Rep-PCR foram factíveis na detecção da diversidade genética. Oito isolados do gênero Enterobacter em secreção conjuntival e, ao mesmo tempo, no humor aquoso, apresentaram distância genética de 0.000. Cinco por cento dos pacientes submetidos à facoemulsificação com implante de LIO apresentaram contaminação do humor aquoso, por Enterobacter spp
Keywords: Cão; Catarata - Cirurgia; Bacterias patogenicas; Reação em cadeia de polimerase; Facoemulsificação; Phacoemulsification